2010
DOI: 10.1001/archneurol.2010.198
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone-Mediated Autophagy Markers in Parkinson Disease Brains

Abstract: To investigate chaperone-mediated autophagy in the pathogenesis of Parkinson disease (PD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
428
2
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 492 publications
(458 citation statements)
references
References 40 publications
21
428
2
7
Order By: Relevance
“…Increased levels of LAMP-2A have been observed in the early stages of PD both in mouse models [54] and in brains of PD patients [52]. However, in advanced stages, reduced levels of LAMP-2A and hsc70 have been detected instead in the dopaminergic neurons of human brain regions [58]. In fact, there seems to be a good correlation between regional deficiency in LAMP-2A, used as a surrogate marker for CMA function, and the selective vulnerability of the brain regions to α-synuclein aggregation [59].…”
Section: Parkinson's Disease (Pd)mentioning
confidence: 99%
“…Increased levels of LAMP-2A have been observed in the early stages of PD both in mouse models [54] and in brains of PD patients [52]. However, in advanced stages, reduced levels of LAMP-2A and hsc70 have been detected instead in the dopaminergic neurons of human brain regions [58]. In fact, there seems to be a good correlation between regional deficiency in LAMP-2A, used as a surrogate marker for CMA function, and the selective vulnerability of the brain regions to α-synuclein aggregation [59].…”
Section: Parkinson's Disease (Pd)mentioning
confidence: 99%
“…19,20 In the context of PD, decreased LAMP2A [21][22][23] and HSPA8/ HSC70 21 protein levels are detected in human post-mortem PD brains, which-given that age is the primary risk factor for disease development 24 -renders LAMP2A abundance a valid target for both disease pathogenesis and therapy. We have previously shown that RNA-interference targeting LAMP2A results in significant accumulation of SNCA in cultured neurons, 17 whereas overexpression of LAMP2A in cell culture models and in dopaminergic neurons of the substantia nigra pars compacta (SNpc) is able to fully rescue neurotoxicity associated with elevated SNCA protein burden.…”
Section: Introductionmentioning
confidence: 99%
“…This disagreement suggests that elimination of this ␣-syn mutant could be enhanced in normal physiological conditions and it might be affected in the context of aging or PD pathogenesis. This hypothesis is supported by several observations reporting a dramatic dysfunction of protein degradation pathway, notably the autophagy pathway, during aging (45,46) and in PD-diseased brains (47,48), which lead to protein accumulation and neuronal loss.…”
Section: Discussionmentioning
confidence: 58%